Structural Profiling of Bacterial Effectors Reveals Enrichment of Host-Interacting Domains and Motifs - Chen, Yangchun Frank; Xia, Yu (Frontiers in Molecular Biosciences, 2021)
Effector proteins are bacterial virulence factors secreted directly into host cells and, through extensive interactions with host proteins, rewire host signaling pathways to the advantage of the pathogen. Despite the crucial role of globular domains as mediators of protein-protein interactions (PPIs), previous structural studies of bacterial effectors are primarily focused on individual domains, rather than domain-mediated PPIs, which limits their ability to uncover systems-level molecular recognition principles governing host-bacteria interactions. Here, we took an interaction-centric approach and systematically examined the potential of structural components within bacterial proteins to engage in or target eukaryote-specific domain-domain interactions (DDIs). Our results indicate that: (1) effectors are 6 times as likely as non-effectors to contain host-like domains that mediate DDIs exclusively in eukaryotes; (2) the average domain in effectors is 7 times as likely as that in non-effectors to co-occur with DDI partners in eukaryotes rather than in bacteria; and (3) effectors are 9 times as likely as non-effectors to contain bacteria-exclusive domains that target host domains mediating DDIs exclusively in eukaryotes. Moreover, in the absence of host-like domains or among pathogen proteins without domain assignment, effectors harbor a higher variety and density of short linear motifs targeting host domains that mediate DDIs exclusively in eukaryotes. Our study lends novel quantitative insight into the structural basis of effector-induced perturbation of host-endogenous PPIs and may aid in the design of selective inhibitors of host-pathogen interactions.